Conductive pigment paste, composite paste, and coating film
The conductive pigment paste, formulated with a specific pigment dispersed resin and conductive carbon with varying particle sizes, addresses the challenges of dispersibility and stability, resulting in a coating film with superior finishing and conductivity.
Patent Information
- Application Number
- JP2021019585
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing conductive pigment pastes face challenges in achieving excellent pigment dispersibility and storage stability at high pigment concentrations, while also ensuring the coating film has superior finishing properties and conductivity.
A conductive pigment paste comprising a specific pigment dispersed resin, conductive carbon with varying average primary particle diameters, and a solvent, where the conductive carbon particles have a specific ratio and are selected from types such as acetylene black, carbon nanotubes, and graphene, to achieve optimal dispersibility and conductivity.
The proposed solution enables a conductive pigment paste with excellent pigment dispersibility and storage stability, even at high concentrations, resulting in a coating film with enhanced finishing properties and conductivity.
Smart Images

Figure 0007646962000001 
Figure 0007646962000002 
Figure 0007646962000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive pigment paste and composite paste that are excellent in pigment dispersibility and storage stability even at high pigment concentrations, and to a coating film that is excellent in finish properties, etc. [Background technology]
[0002] Conventionally, paste-like pigment dispersions in which a pigment is dispersed in a mixture of a pigment dispersing resin and a solvent have been widely used in the fields of paints, battery electrodes, coating materials, coating materials, electromagnetic shields, display panels, touch screen panels, colored films, colored sheets, decorative materials, protective materials, magnet modifiers, printing inks, device members, electronic device members, printed wiring boards, solar cells, functional rubber members, resin molded films, etc. Furthermore, conductive pigments, conductive polymers, etc. are contained in these materials to impart functions such as electrostatic paintability, conductivity, electromagnetic shielding properties, and antistatic properties. In these fields, there is an increasing demand for improved performance such as pigment dispersibility, storage stability, coatability, electrical conductivity, finishability, and solvent resistance. For this reason, pigment dispersing resins and pigment pastes having excellent pigment dispersing ability and excellent pigment dispersion stability that prevents re-aggregation of pigment particles in the formed pigment dispersion are being developed.
[0003] When designing a pigment paste, it is important to prepare a highly concentrated and uniformly dispersed pigment paste using a small amount of pigment dispersion resin so that the pigment dispersion resin does not adversely affect the conductive properties of the final product itself, such as the coating film, or from the perspective of reducing the amounts of solvent and pigment dispersion resin used and reducing the energy used during drying. For example, Patent Document 1 discloses a conductive pigment paste containing carbon-coated metal particles, which are made by using metal particles as a core material and coating the surfaces of the metal particles with carbon, a binder resin, and a solvent. However, since it uses expensive conductive materials such as silver and copper, it cannot be used as a general-purpose material. Patent Document 2 describes a mixture obtained by mixing a water-soluble xylan aqueous solution in which carbon nanotubes are dispersed with a carbon black acetone dispersion. However, this mixture (paste) is for forming a carbon composite filler to be added to a resin, and is not for applying to form a coating film. Furthermore, no consideration is given to the dispersibility of carbon nanotubes and carbon black. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-22598 A [Patent Document 2] International Publication No. 2015 / 064708 Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to provide a conductive pigment paste and composite paste which are excellent in pigment dispersibility and storage stability even at a high pigment concentration, and a coating film which is excellent in finish properties, etc. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the inventors have found that the above problems can be solved by a conductive pigment paste containing a specific pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), and have thus completed the present invention. That is, the present invention provides the following conductive pigment paste, composite paste, and coating film. Item 1: A conductive pigment paste containing a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2, the ratio of the two, X1 / X2, is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; The content ratio of conductive carbon (B-1) and conductive carbon (B-2) is 1 / 99 to 99 / 1. Conductive pigment paste. Item 2: The conductive carbon (B-1) and the conductive carbon (B-2) are each selected from the group consisting of acetylene black, furnace black, thermal black, ketjen black, carbon nanotubes, graphene, and graphite. The conductive pigment paste according to item 1. Item 3: The BET specific surface area of both the conductive carbon (B-1) and the conductive carbon (B-2) is 10 to 250 m 2 Item 3. The conductive pigment paste according to item 1 or 2, wherein the conductive pigment paste has a molecular weight of 1.0 to 1.0 g. Item 4: The conductive pigment paste according to any one of Items 1 to 3, wherein the content of the conductive pigment (B) is 60 mass% or more based on the solid content of the conductive pigment paste, and the total amount of the conductive carbon (B-1) and the conductive carbon (B-2) is 50 mass% or more based on the mass of the conductive pigment (B). Item 5: The conductive pigment paste according to any one of Items 1 to 4, wherein the conductive pigment paste is diluted with a solvent and has an average particle size (D50) of 300 to 1200 nm, the average particle size being measured by a volume-based particle size distribution measurement method using a laser diffraction scattering method. Item 6: The conductive pigment paste according to any one of Items 1 to 5, wherein the conductive pigment paste is diluted with a solvent and a frequency distribution curve obtained by measuring a volumetric particle size distribution by a laser diffraction scattering method has at least two peaks. Item 7: The conductive pigment paste according to any one of Items 1 to 6, wherein the pigment dispersion resin (A) has at least one polar functional group selected from the group consisting of an amide group, an imide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphoric acid group, a silanol group, and an amino group, and the pigment dispersion resin (A) has a polar functional group concentration of 10 to 23 mmol / g. Item 8: The conductive pigment paste according to any one of Items 1 to 7, wherein a solubility parameter ΔA of the pigment dispersion resin (A) and a solubility parameter ΔC of the solvent (C) satisfy a relationship of |ΔA-ΔC|<2.0. Item 9: The conductive pigment paste according to any one of Items 1 to 8, wherein the solid content of the pigment dispersion resin (A) is 0.1 to 20 mass% based on the total amount of solids in the conductive pigment paste. Item 10: The conductive pigment paste according to any one of Items 1 to 9, wherein the pigment dispersion resin (A) has a solubility parameter ΔA of 9.3 or more, and the solvent (C) has a solubility parameter ΔC of 10.4 to 15.0. Item 11: The conductive pigment paste according to any one of Items 1 to 10, further comprising 0.01 to 1.0 mass % of a highly polar, low molecular weight component based on the conductive pigment (B). Item 12: The conductive pigment paste according to any one of Items 1 to 11, further comprising a film-forming resin (D) having a weight-average molecular weight of 100,000 or more and / or a solubility parameter ΔD of less than 10.0. Item 13: A coating composition comprising a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), Average primary particle diameter X1 of conductive carbon (B-1) and Record The ratio X1 / X2 of the average primary particle diameter X2 of the conductive carbon (B-2) is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; The content ratio of conductive carbon (B-1) and conductive carbon (B-2) is 1 / 99 to 99 / 1. A method for dispersing a conductive pigment paste, comprising dispersing the conductive pigment paste substantially without using a media. Item 14: A composite paste comprising the conductive pigment paste according to any one of items 1 to 12 and at least one kind of electrode active material. Item 15: A coating film obtained by applying the conductive pigment paste according to any one of items 1 to 12 to a substrate. Item 16: A battery electrode layer obtained by applying the composite paste according to item 14 to a current collector. Effect of the Invention
[0007] According to the present invention, it is possible to provide a conductive pigment paste and a composite paste which are excellent in pigment dispersibility and storage stability even at a high pigment concentration. Furthermore, the present invention can provide a coating film that is excellent in finish and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described in detail. It should be understood that the present invention is not limited to the following embodiments, but includes various modified examples that are implemented within the scope that does not deviate from the gist of the present invention. The "composite paste" of the present invention is a liquid composition containing a conductive pigment paste, and can be called a "coating material". The composite paste applied to a substrate and dried is called a "coating film". When the coating film is used for a battery electrode, it can be called an "electrode layer". Here, the solubility parameter is also commonly called the SP value (solubility parameter), and is a scale that indicates the degree of hydrophilicity or hydrophobicity (polarity) of a solvent or resin. It is also an important scale for judging the solubility and compatibility between a solvent and a resin, and between resins. When the solubility parameter values are close (the absolute value of the difference in solubility parameters is small), the solubility and compatibility are generally good. In one embodiment of the present invention, a conductive pigment paste having a conductive pigment (B) in a suitable dispersed state is first prepared, and then various components are added to the conductive pigment paste to produce a composite paste in order to obtain a coating film that satisfies various performance requirements.
[0009] [Conductive pigment paste] The conductive pigment paste of the present invention is a conductive pigment paste containing a pigment dispersing resin (A), a conductive pigment (B), and a solvent (C), The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), the ratio X1 / X2 of the average primary particle size or average diameter X1 of the conductive carbon (B-1) to the average primary particle size or average diameter X2 of the conductive carbon (B-2) is 1.2 to 2.5 (preferably 1.3 to 2.0, more preferably 1.4 to 1.7), and both X1 and X2 are 100 nm or less; The content ratio of the conductive carbon (B-1) and the conductive carbon (B-2) is 1 / 99 to 99 / 1.
[0010] <Pigment dispersing resin (A)> The pigment dispersing resin (A) is not particularly limited as long as it is a resin having a pigment dispersing function. Examples of the pigment dispersion resin (A) include acrylic resins, polyester resins, epoxy resins, polyether resins, alkyd resins, urethane resins, polyvinyl alcohol, polyvinyl acetal, polyvinylpyrrolidone, polyvinyl acetate, silicone resins, polycarbonate resins, silicate resins, chlorine-based resins, fluorine-based resins, resins having polycyclic aromatic hydrocarbon groups, and composite resins thereof. These resins can be used alone or in combination of two or more.
[0011] The pigment dispersing resin (A) preferably contains at least one polar functional group selected from the group consisting of an amide group, an imide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphoric acid group, a silanol group, and an amino group. The polar functional group concentration of the pigment dispersing resin (A) is, for example, 10 to 23 mmol / g, preferably 15 to 22.9 mmol / g, and more preferably 20 to 22.8 mmol / g, from the viewpoints of dispersibility, storage stability, and compatibility with the solvent.
[0012] From the viewpoint of imparting sufficient film-forming properties to a coating film formed from the paste without impairing the excellent finish and electrical conductivity of the coating film, the pigment dispersion resin (A) preferably contains a vinyl (co)polymer (A-1) obtained by polymerizing or copolymerizing a monomer containing a polymerizable unsaturated group-containing monomer of the following formula (1). Note that the "(co)polymer" of the present invention includes both a polymer obtained by polymerizing one type of monomer and a copolymer obtained by copolymerizing two or more types of monomers. C(-R) 2 =C(-R) 2 ...Equation (1) [In formula (1), R may be the same or different and is a hydrogen atom or an organic group.]
[0013] The vinyl (co)polymer (A-1) may have in its structure "-CH 2 It is preferable that the polymer contains a structural unit represented by -CH(-X)- (wherein X is an organic group having a polar functional group), and the polar functional group X in the structural unit is at least one polar functional group selected from the group consisting of an amide group, an imide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphoric acid group, a silanol group, and an amino group. Examples of the vinyl (co)polymer (A-1) include hydroxyl group-containing vinyl (co)polymer, carboxyl group-containing vinyl (co)polymer, pyrrolidone group-containing vinyl (co)polymer, amide group-containing vinyl (co)polymer, sulfonic acid group-containing vinyl (co)polymer, phosphoric acid group-containing vinyl (co)polymer, amino group-containing vinyl (co)polymer, etc. These (co)polymers may be used alone or in combination of two or more.
[0014] Examples of hydroxyl group-containing vinyl (co)polymers include polyhydroxyethyl (meth)acrylate, polyvinyl alcohol, vinyl alcohol-fatty acid vinyl copolymer, vinyl alcohol-ethylene copolymer, vinyl alcohol-(N-vinylformamide) copolymer, copolymers of hydroxyethyl (meth)acrylate and other polymerizable unsaturated group-containing monomers, etc. The vinyl alcohol units in the (co)polymer may be obtained by (co)polymerizing fatty acid vinyl units and then hydrolyzing them in part or in whole. Examples of the carboxyl group-containing vinyl (co)polymer include a polymer of (meth)acrylic acid, and a copolymer of poly(meth)acrylic acid and another polymerizable unsaturated group-containing monomer. Examples of the pyrrolidone group-containing vinyl (co)polymer include polyvinylpyrrolidone, N-vinyl-2-pyrrolidone-ethylene copolymer, and N-vinyl-2-pyrrolidone-vinyl acetate copolymer. Examples of the amide group-containing vinyl (co)polymer include a polymer of (meth)acrylamide, and a copolymer of (meth)acrylamide and another polymerizable unsaturated group-containing monomer. Examples of the sulfonic acid group-containing vinyl (co)polymer include polymers of allylsulfonic acid or styrenesulfonic acid, and copolymers of allylsulfonic acid and / or styrenesulfonic acid with other polymerizable unsaturated group-containing monomers. Examples of the phosphoric acid group-containing vinyl (co)polymer include a polymer of (meth)acryloyloxyalkyl acid phosphate, and a copolymer of (meth)acryloyloxyalkyl acid phosphate with another polymerizable unsaturated group-containing monomer. Examples of the amino group-containing vinyl (co)polymer include polyvinylamine, polyallylamine, a polymer of dimethylaminoethyl (meth)acrylate, and a copolymer of dimethylaminoethyl (meth)acrylate with other polymerizable unsaturated group-containing monomers.
[0015] From the viewpoint of improving dispersibility and reducing the surface resistivity of the coating film, the vinyl (co)polymer (A-1) is preferably a hydroxyl group-containing polyvinyl (co)polymer, a carboxyl group-containing polyvinyl (co)polymer, or a pyrrolidone group-containing polyvinyl (co)polymer, more preferably a hydroxyl group-containing polyvinyl (co)polymer, and even more preferably a polyvinyl alcohol (co)polymer. In addition, with regard to the above-mentioned polyvinyl alcohol (co)polymer, when the (co)polymer contains monomer units of “vinyl acetate” and “vinyl alcohol”, it can also be referred to as a “vinyl acetate-vinyl alcohol copolymer” in this specification. The vinyl (co)polymer (A-1) is the above-mentioned "-CH 2In addition to the structural unit represented by -CH(-X)-, the copolymer may contain a structural unit derived from a copolymerizable polymerizable unsaturated group-containing monomer, if necessary. Examples of the copolymerizable polymerizable unsaturated group-containing monomer include vinyl carboxylate ester monomers such as vinyl formate, vinyl acetate, vinyl propionate, isopropenyl acetate, vinyl valerate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl versatate, and vinyl pivalate; olefins such as ethylene, propylene, and butylene; aromatic vinyls such as styrene and α-methylstyrene; methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dimethyl fumarate, dimethyl maleate, diethyl maleate, and itaconic acid. Examples of the monomers include ethylenically unsaturated carboxylic acid alkyl ester monomers such as diisopropyl; vinyl ether monomers such as methyl vinyl ether, n-propyl vinyl ether, isobutyl vinyl ether, and dodecyl vinyl ether; ethylenically unsaturated nitrile monomers such as (meth)acrylonitrile; halogenated vinyl monomers or vinylidene monomers such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; quaternary ammonium group-containing monomers such as 3-(meth)acrylamidopropyltrimethylammonium chloride; vinyltrimethoxysilane, N-vinylformamide, and (meth)acrylamide. These monomers can be used alone or in combination of two or more.
[0016] The vinyl (co)polymer (A-1) can be produced by a polymerization method known per se. For example, it is preferable to use solution polymerization, but it is not limited thereto, and bulk polymerization, emulsion polymerization, suspension polymerization, etc. may also be used. When carrying out solution polymerization, it may be continuous polymerization or batch polymerization, and the monomer may be charged all at once or in portions, or may be added continuously or intermittently. The polymerization initiator used in the solution polymerization is not particularly limited, but specific examples thereof include known radical polymerization initiators such as azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and azobis(4-methoxy-2,4-dimethylvaleronitrile); peroxides such as acetyl peroxide, benzoyl peroxide, lauroyl peroxide, acetylcyclohexylsulfonyl peroxide, and 2,4,4-trimethylpentyl-2-peroxyphenoxyacetate; percarbonate compounds such as diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as t-butyl peroxyneodecanate, α-cumyl peroxyneodecanate, and t-butyl peroxyneodecanate; and azobisdimethylvaleronitrile and azobismethoxyvaleronitrile. The polymerization reaction temperature is not particularly limited, but can usually be set within the range of about 30 to 200°C.
[0017] The degree of polymerization of the vinyl (co)polymer (A-1) is preferably from 100 to 4,000, more preferably from 100 to 3,000, and even more preferably from 150 to 700. The weight average molecular weight of the vinyl (co)polymer (A-1) is preferably from 1,000 to 200,000, more preferably from 2,000 to 100,000, and even more preferably from 7,000 to 30,000. After completion of the synthesis, the vinyl (co)polymer (A-1) can be converted into a solid or into a resin solution in which any solvent has been replaced by removing the solvent and / or replacing the solvent. The method for removing the solvent may be performed by heating at normal pressure or under reduced pressure. The method for replacing the solvent may be performed by adding a replacement solvent at any stage before, during, or after the removal of the solvent.
[0018] The solubility parameter ΔA of the pigment dispersing resin (A) is preferably 9.3 or more, more preferably 10.0 to 13.0, and even more preferably 11.0 to 12.5, from the viewpoints of dispersibility, storage stability, and compatibility with the solvent. The solubility parameter of a resin is numerically quantified based on a turbidity measurement method known to those skilled in the art, and specifically, can be determined in accordance with the KWSUH and JMCORBETT formula (Journal of Applied Polymer Science, 12, 2359, 1968). When two or more types of pigment dispersing resin (A) are used, the "solubility parameter ΔA of the pigment dispersing resin (A)" is the total value obtained by multiplying the solubility parameter value of each resin by the mass fraction.
[0019] The solid content of the pigment dispersion resin (A) in the conductive pigment paste is not particularly limited, but is, for example, 0.1 to 20 mass%, preferably 0.5 to 15 mass%, and more preferably 1.5 to 10 mass%, based on the total solid content of the paste. By setting the content within such a range, the viscosity during pigment dispersion, pigment dispersibility, storage stability, production efficiency, conductivity, etc. can be made suitable.
[0020] <Conductive pigment (B)> The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), and when the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, where X1>X2, the ratio of the two, X1 / X2, is 1.2 to 2.5, both X1 and X2 are 100 nm or less, and the content ratio of the conductive carbon (B-1) to the conductive carbon (B-2) is 1 / 99 to 99 / 1 (preferably 10 / 90 to 90 / 10). If the X1 / X2 ratio is less than 1.2, the conductive carbon may have a substantially unimodal particle size distribution, resulting in a decrease in conductivity.If the X1 / X2 ratio exceeds 2.5, the difference in the average primary particle size or average diameter of the conductive carbon may be too large, resulting in a decrease in dispersibility, finish, and conductivity.
[0021] In the present invention, the reason or principle for improving conductivity by using conductive carbon (B-1) and conductive carbon (B-2) in combination, which have different average primary particle sizes or average diameters and have a specific relationship, is not particularly clear. The present inventors believe that conductive carbon (B-1) with a large average primary particle size or average diameter forms a thick conductive path, while conductive carbon (B-2) with a small average primary particle size or average diameter effectively fills the gaps, thereby forming a good conductive path and improving conductivity.
[0022] The conductive carbon (B-1) and the conductive carbon (B-2) are each at least one selected from the group consisting of acetylene black, furnace black, thermal black, ketjen black, carbon nanotubes, graphene, and graphite. In the conductive carbon (B-1) and conductive carbon (B-2), in the case of acetylene black, furnace black, thermal black, ketjen black, graphene, and graphite, the average primary particle size is used, and in the case of carbon nanotubes, the average diameter is used. The conductive carbon (B-1) is preferably one or more selected from the group consisting of acetylene black, carbon nanotubes, and graphene, more preferably acetylene black and / or carbon nanotubes, and particularly preferably acetylene black. The conductive carbon (B-2) is preferably at least one selected from the group consisting of acetylene black, carbon nanotubes, and graphene, more preferably acetylene black and / or carbon nanotubes, and particularly preferably acetylene black.
[0023] The average primary particle diameters of the conductive carbon (B-1) and the conductive carbon (B-2) are both 100 nm or less, preferably within the range of 10 to 80 nm, and more preferably within the range of 20 to 52 nm, in consideration of the relationship between viscosity and conductivity. Here, the average primary particle diameter in the present invention refers to the average diameter of primary particles obtained by observing a pigment under an electron microscope, calculating the projected area of each of 100 particles, calculating the diameter of a circle assuming an area equal to the projected area, and then calculating the simple average of the diameters of the 100 particles. Note that, if the pigment is in an aggregated state, the calculation is performed using the primary particles that make up the aggregated particles.
[0024] The DBP oil absorption (dibutyl phthalate oil absorption) of the conductive carbon (B-1) is not particularly limited, but is preferably, for example, 60 to 1,000 ml / 100 g, and more preferably 150 to 800 ml / 100 g, in view of the relationship between pigment dispersibility and electrical conductivity. The DBP oil absorption (dibutyl phthalate oil absorption) of the conductive carbon (B-2) is not particularly limited, but is preferably, for example, 60 to 1,000 ml / 100 g, and more preferably 150 to 800 ml / 100 g, in view of the relationship between pigment dispersibility and electrical conductivity. The BET specific surface area of the conductive carbon (B-1) is not particularly limited, but is, for example, 1 to 500 m in relation to the viscosity and the conductivity. 2 / g, preferably 10 to 250 m 2 The BET specific surface area of the conductive carbon (B-2) is not particularly limited, but is preferably 1 to 500 m / g, for example, in view of the relationship between viscosity and conductivity. 2 / g, preferably 10 to 250 m 2 / g. In addition, the BET specific surface area of both the conductive carbon (B-1) and the conductive carbon (B-2) is preferably 10 to 250 m 2 / g, and 12 to 200m 2 / g is more preferable, and 20 to 150m 2 It is particularly preferred that the molecular weight is / g.
[0025] The conductive pigment (B) is preferably basic in terms of pigment dispersibility, and for example, the pH is preferably 7.5 or higher, more preferably 8.0 to 12.0, and even more preferably 8.5 to 11.0. When the conductive pigment (B) contains carbon black, it is preferable that the primary particles of the carbon black form a chain structure from the viewpoint of conductivity, and the structure index is more preferably within the range of 1.5 to 4.0, and particularly preferably within the range of 1.7 to 3.2. The structure itself can be relatively easily observed in images taken with an electron microscope, but the structure index is a numerical value that quantifies the degree of structure. The structure index is generally calculated by multiplying the DBP oil absorption (ml / 100g) by the specific surface area (m 2 It can be defined as the value obtained by dividing the DBP absorption by the total DBP content by the total DBP content (1.5 / g). If the structure index is less than 1.5, the structure is not well developed and sufficient conductivity cannot be obtained, and if it exceeds 4.0, the particle size is large relative to the DBP oil absorption, so the conductive paths are reduced, resulting in insufficient conductivity or an increase in the viscosity of the composite paste.
[0026] The content of the conductive pigment (B) is, for example, 60 mass% or more, preferably 60 to 99.9 mass%, more preferably 65 to 98.5 mass%, and particularly preferably 70 to 97 mass%, based on the total solid content of the conductive pigment paste, from the viewpoints of conductivity and pigment dispersibility. The total amount of the conductive carbon (B-1) and the conductive carbon (B-2) is, for example, 50 mass% or more, preferably 50 to 100 mass%, more preferably 60 to 100 mass%, and more preferably 70 to 100 mass%, based on the mass of the conductive pigment (B).
[0027] In the conductive pigment paste of the present invention, the conductive pigment other than the conductive carbon (B-1) and the conductive carbon (B-2) is not particularly limited as long as it can impart conductivity to the coating film formed, and examples thereof include pigments in the form of particles, flakes, and fibers (including whiskers).Specific examples thereof include metal powders such as silver, nickel, copper, graphite, and aluminum, antimony-doped tin oxide, phosphorus-doped tin oxide, needle-shaped titanium oxide surface-coated with tin oxide / antimony, antimony oxide, zinc antimonate, indium tin oxide, pigments in which the surface of carbon or graphite whiskers is coated with tin oxide, etc., pigments in which the surface of flake-shaped mica is coated with at least one conductive metal oxide selected from the group consisting of tin oxide, antimony-doped tin oxide, tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), phosphorus-doped tin oxide, and nickel oxide, and pigments having conductivity containing tin oxide and phosphorus on the surface of titanium dioxide particles.The conductive pigment (B) can be used in combination of two or more types.
[0028] <Solvent (C)> The solvent (C) is not particularly limited as long as it can dissolve the pigment dispersion resin (A) and disperse the conductive pigment (B). For example, hydrocarbon solvents such as n-butane, n-hexane, n-heptane, n-octane, cyclopentane, cyclohexane, and cyclobutane; aromatic solvents such as toluene and xylene; ketone solvents such as methyl isobutyl ketone; ether solvents such as n-butyl ether, dioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and diethylene glycol; ethyl acetate, n-butyl acetate, isobutyl acetate, and ethylene glycol monomethyl ether acetate. Examples of suitable solvents include ester-based solvents such as butyl carbitol acetate, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, and other ketone-based solvents, alcohol-based solvents such as ethanol, isopropanol, n-butanol, sec-butanol, isobutanol, and other amide-based solvents such as Equamide (trade name: manufactured by Idemitsu Kosan Co., Ltd., amide-based solvent), N,N-dimethylformamide, N,N-dimethylacetamide, N-methylformamide, N-methylacetamide, N-methylpropioamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone. These solvents can be used alone or in combination of two or more. In the present invention, from the viewpoints of the solubility of the pigment dispersing resin (A) and the dispersibility and storage stability of the conductive pigment paste, it is preferable to contain a solvent having a polar functional group such as a hydroxyl group, a carboxyl group, an amide group, an amino group, or an ether group. Among these, high boiling point polar solvents are preferred, and amide solvents are particularly preferred.
[0029] The solubility parameter (SP value) of the solvent (C) is set to 10.4 to 15.0 (cal / cm) from the viewpoints of the solubility of the pigment dispersion resin (A), the dispersibility of the conductive pigment paste, and storage stability. 3 ) 1 / 2 It is preferable that the range is 10.5 to 13.0 (cal / cm 3 ) 1 / 2 It is more preferable that the range is within the range. The solubility parameter ΔA of the pigment dispersion resin (A) and the solubility parameter ΔC of the solvent (C) preferably satisfy the relationship |ΔA-ΔC|<2.0, more preferably |ΔA-ΔC|<1.5, and even more preferably |ΔA-ΔC|<1.3.
[0030] The solubility parameter of a solvent can be determined according to the method described in "Polymer Handbook" VII Solubility Parameter Values, pp. 519-559, edited by J. Brandrup and EH Immergut (John Wiley & Sons, 3rd Edition, 1989). When two or more solvents are combined and used as a mixed solvent, the solubility parameter of the mixed solvent can be determined experimentally, or, as a simple method, it can be determined by the sum of the products of the molar fractions and the solubility parameters of the individual liquid solvents. The "solubility parameter of the solvent (C)" in the present invention refers to the solubility parameter of all the solvents (mixed solvent) contained in the conductive pigment paste.
[0031] <Conductive pigment paste> The conductive pigment paste of the present invention may contain other components, if necessary, in addition to the pigment dispersing resin (A), the conductive pigment (B) and the solvent (C). Examples of other components include resins other than the pigment dispersion resin (A), the highly polar low molecular weight component (E), pigments other than the conductive pigment (B), neutralizers, defoamers, preservatives, rust inhibitors, plasticizers, etc.
[0032] (Resins other than pigment dispersion resin (A)) The resin other than the pigment dispersion resin (A) is not particularly limited, but is preferably a pigment dispersion resin and / or a film-forming resin. For example, acrylic resin other than the pigment dispersion resin (A), polyester resin, epoxy resin, polyether resin, alkyd resin, urethane resin, silicone resin, polycarbonate resin, silicate resin, chlorine-based resin, fluorine-based resin, polyvinylpyrrolidone resin, polyvinyl alcohol resin, polyvinyl acetal resin, styrene-based resin, diene-based resin, polyolefin-based resin, and composite resins thereof can be mentioned. These resins can be used alone or in combination of two or more.
[0033] (Film-forming resin (D)) The conductive pigment paste of the present invention preferably contains a film-forming resin (D) as a resin other than the pigment dispersing resin (A). The film-forming resin (D) is not particularly limited as long as it can impart film-forming properties to the coating film. For example, it is preferably a low-polarity resin that does not substantially contain the polar functional group that the pigment dispersion resin (A) has. Here, the polar functional group concentration is, for example, less than 10 mmol / g, preferably 5 mmol / g or less, more preferably 1 mmol / g or less. Examples of the film-forming resin (D) include epoxy resins, urethane resins, chlorine-based resins, fluorine-based resins, styrene-based resins, diene-based resins, polyolefin-based resins, and composite resins thereof, etc. These resins can be used alone or in combination of two or more. The film-forming resin (D) may be contained when the pigment is dispersed, or may be added after the pigment is dispersed.
[0034] The weight average molecular weight of the film-forming resin (D) is preferably 100,000 or more, and more preferably 500,000 to 3,000,000, from the viewpoints of adhesion to the substrate, reinforcement of the coating properties, and solvent resistance. The solubility parameter of the film-forming resin (D) is preferably less than 10, more preferably less than 9.3.
[0035] When the conductive pigment paste of the present invention contains a film-forming resin (D), from the viewpoints of the solubility and storage stability of the resin, the solubility parameter ΔD of the film-forming resin (D) and the solubility parameter ΔC of the solvent (C) preferably satisfy the relationship |ΔD-ΔC|<2.5, and more preferably satisfy the relationship 0≦|ΔD-ΔC|≦2.2.
[0036] (High polar low molecular weight component (E)) The conductive pigment paste of the present invention preferably contains a highly polar, low-molecular-weight component (E) from the viewpoint of improving one or more of the properties of the conductive pigment, namely, wettability, dispersibility, and storage stability. The highly polar low molecular weight component (E) is preferably basic or acidic, and may be a salt in part or in whole. In particular, when the pigment is acidic, a base-containing low molecular weight component is preferred, and when the pigment is basic, an acid group-containing low molecular weight component is preferred. From the viewpoint of water resistance and the like, it is preferable that the highly polar low molecular weight component does not remain as much as possible in the coating film after the solvent is evaporated (heat dried).
[0037] As the highly polar low molecular weight component (E), for example, one or more types of acidic highly polar low molecular weight components selected from organic acids and inorganic acids can be used. In addition, one or more types of basic highly polar low molecular weight components selected from organic bases and inorganic bases can be used. Examples of organic acids include organic carboxylic acids (formic acid, glutamic acid, acetic acid, propionic acid, benzoic acid, phthalic acid, etc.), organic sulfonic acids (benzenesulfonic acid, etc.), etc.; examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc.; examples of organic bases include amine compounds (pyridine, triethylamine, diazabicycloundecene, aniline, etc.); and examples of inorganic bases include metal hydroxides (sodium hydroxide, potassium hydroxide, etc.), ammonia, etc., including acid anhydrides and hydrates. The content of the highly polar, low-molecular-weight component (E) is preferably from 0.01 to 2.0% by mass, and more preferably from 0.02 to 1.0% by mass, based on the conductive pigment (B).
[0038] (Pigments other than conductive pigments (B)) The conductive pigment paste of the present invention may contain a non-conductive pigment other than the conductive pigment (B). Examples of pigments other than the conductive pigment (B) include white pigments such as titanium white and zinc oxide; blue pigments such as cyanine blue and indanthrene blue; green pigments such as cyanine green and verdigris; organic red pigments such as azo and quinacridone, red pigments such as red iron oxide; organic yellow pigments such as benzimidazolone, isoindolinone, isoindoline, and quinophthalone, and yellow pigments such as titanium yellow and yellow lead. These pigments can be used alone or in combination of two or more.
[0039] Pigments other than these conductive pigments (B) can be used for purposes such as color adjustment and reinforcement of the physical properties of the film, as long as the use does not significantly impair the conductivity. They may be dispersed simultaneously with the pigment dispersion resin (A) and the conductive pigment (B), or may be mixed as a pigment or pigment paste after dispersing the pigment dispersion resin (A) and the conductive pigment (B) to prepare a paste. The content of pigments other than the conductive pigment (B) is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less, based on the total amount of pigments in the conductive pigment paste, and it is particularly preferable that the pigments are substantially not contained.
[0040] (Water content) From the viewpoints of dispersibility and preventing deterioration or hydrolysis of the resin, the conductive pigment paste of the present invention preferably does not substantially contain water. Here, "substantially does not contain water" means that the water content is usually 1 mass % or less, preferably 0.5 mass % or less, and particularly preferably 0.1 mass % or less, based on the total amount of the conductive pigment paste. In the present invention, the water content of the conductive pigment paste can be measured by Karl Fischer coulometric titration. Specifically, the water content can be measured using a Karl Fischer moisture meter (manufactured by Kyoto Electronics Manufacturing Co., Ltd., product name: MKC-610) with the temperature of a moisture vaporizer (manufactured by Kyoto Electronics Manufacturing Co., Ltd., product name: ADP-611) attached to the device set to 130° C.
[0041] (Average particle diameter (D50)) The conductive pigment paste of the present invention has an average particle size (D50) obtained by diluting the conductive pigment paste with a solvent and measuring the volume-based particle size distribution by a laser diffraction scattering method, which is preferably within the range of 300 to 1,200 nm, more preferably within the range of 400 to 1,100 nm.
[0042] (Particle size distribution of conductive pigment (B)) As for the particle size distribution of the conductive pigment (B) in the conductive pigment paste obtained by the above-mentioned composition, it is preferable that the conductive pigment paste is overdiluted with the solvent (C) and a frequency distribution curve obtained by measuring the volume-based particle size distribution by a laser diffraction scattering method has at least two peaks.
[0043] When the particle size distribution of the conductive pigment (B) has at least two peaks and satisfies the above-mentioned conditions, the conductive pigment in the conductive pigment paste can form a structure while having appropriate fluidity, and the coating film can have good finish properties and conductivity. In the present invention, the volume-based particle size distribution measurement by the laser diffraction scattering method was performed using a particle size distribution measuring device (manufactured by Microtrack-Bell, product name: Microtrack MT3000).
[0044] In the conductive pigment paste of the present invention, when the average particle size (D50) of the primary particles of the conductive pigment (B) is taken as 1, the average particle size (D50) obtained by diluting the conductive pigment paste with a solvent and measuring the volume-based particle size distribution by a laser diffraction scattering method is preferably 10 to 50, more preferably 18 to 32. In the particle size distribution measurement, when the conductive pigment paste contains a pigment other than the conductive pigment (B), the conductive pigment paste prepared using only the conductive pigment (B) is to be measured.
[0045] [How to disperse pigments in conductive pigment paste] The pigment dispersion method for the conductive pigment paste of the present invention includes dispersing components of a pigment paste containing a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), the conductive pigment (B) containing conductive carbon (B-1) and conductive carbon (B-2), a ratio X1 / X2 of an average primary particle size or average diameter X1 of the conductive carbon (B-1) to an average primary particle size or average diameter X2 of the conductive carbon (B-2) being 1.2 to 2.5, X1 and X2 both being 100 nm or less, and a content ratio of the conductive carbon (B-1) to the conductive carbon (B-2) being 1 / 99 to 99 / 1.
[0046] The dispersion of each of the components constituting the conductive pigment paste is not particularly limited, and the components can be uniformly mixed and dispersed using a conventionally known dispersing machine such as a paint shaker, a sand mill, a ball mill, a pebble mill, an LMZ mill, a DCP pearl mill, a planetary ball mill, a homogenizer, a twin-screw kneader, or a thin film rotary high-speed mixer (product names: Clearmix, Filmix, etc.). Among these, in the present invention, from the viewpoint of the conductivity of the coating film, it is preferable not to disperse the conductive carbon (B-1) and conductive carbon (B-2) contained in the conductive pigment (B) finely to the extent of primary particles, and it is preferable to disperse them substantially without using media.
[0047] [Composite paste (coating material)] The composite paste used in the present invention contains as essential components the pigment dispersion resin (A), the conductive pigment (B), and the solvent (C) contained in the conductive pigment paste, and can be obtained by further adding other resins, pigments, solvents, additives, and other components to the conductive pigment paste as necessary.
[0048] Examples of the resin include acrylic resin, polyester resin, epoxy resin, polyether resin, alkyd resin, urethane resin, silicone resin, polycarbonate resin, silicate resin, chlorine-based resin, fluorine-based resin, polyvinylpyrrolidone resin, polyvinyl alcohol resin, polyvinyl acetal resin, and composite resins thereof, etc. These resins can be used alone or in combination of two or more.
[0049] Examples of the pigment include color pigments, luster pigments, extender pigments, rust-preventive pigments, and metal particles. These pigments can be used alone or in combination of two or more. In particular, when the composite paste is used as a material for a battery electrode layer, it is preferable that the composite paste contains an electrode active material. Examples of the electrode active material include lithium nickel oxide (LiNiO 2 ), lithium manganate (LiMn 2 O 4 ), lithium cobalt oxide (LiCoO 2 ), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 These electrode active materials may be used alone or in combination of two or more. When an electrode active material is contained, the solid content of the electrode active material in the solid matter of the composite paste is usually 70 to 99.9 mass %, preferably 80 to 99 mass %, which is suitable from the standpoint of battery capacity, battery resistance, etc.
[0050] The solvent is not particularly limited, and the same solvents as the above-mentioned solvent (C) can be suitably used. The above-mentioned solvents can be used alone or in combination of two or more kinds. Examples of the additives include neutralizing agents, pigment dispersants, defoamers, preservatives, rust inhibitors, plasticizers, and viscosity adjusters.
[0051] The content of the pigment dispersion resin (A) in the composite paste is usually 0.01 to 80 mass%, preferably 0.02 to 50 mass%, more preferably 0.05 to 20 mass%, and particularly preferably 0.08 to 10 mass%, based on the total amount of solids in the composite paste, from the viewpoints of viscosity during pigment dispersion, pigment dispersibility, storage stability, production efficiency, conductivity, etc. The composite paste can be prepared by uniformly mixing or dispersing the above-mentioned components using a conventionally known stirrer or disperser, such as a disperser, a paint shaker, a sand mill, a ball mill, a pebble mill, an LMZ mill, a DCP pearl mill, a planetary ball mill, a homogenizer, a twin-screw kneader, or a thin film swirling high-speed mixer.
[0052] [Coating film (electrode layer)] The composite paste is applied (coated) onto an object to be coated to form a coating film. In the present invention, a coating film refers to a solid film formed by applying a liquid composite paste to a substrate (substrate) and then heating and drying. The film can be peeled off from the substrate to obtain a conductive film, or it can be applied to both sides of a plate-shaped substrate (substrate) to obtain a conductive material. The substrate is not particularly limited, and examples thereof include metal materials, various plastic materials, inorganic materials such as glass, cement, concrete, wood, fiber materials (paper, cloth, etc.), and composite materials of these. Furthermore, these substrates may be degreased, surface-treated, etc., as necessary. The battery electrode layer is preferably applied (coated) to a current collector. The electrode layer can be used, for example, as a positive electrode or a negative electrode of a lithium ion battery.
[0053] The coating method is not particularly limited as long as it allows coating within a certain film thickness range, and examples include roller coating, brush coating, atomization coating, dipping coating, applicator coating, shower coat coating, roll coater coating, and die coater coating. The film thickness is preferably 1 to 200 μm, more preferably 2 to 150 μm, in terms of dry film thickness. The drying temperature is preferably from 60 to 300°C, and more preferably from 80 to 200°C. By the heat drying, it is preferable that 80% or more of the solvent contained in the composite paste is removed, more preferably 90% or more, and particularly preferably 95% or more. In addition, when a highly polar low molecular weight component is contained, it is preferable that a part or all of the solvent is removed by the heat drying. EXAMPLES
[0054] The present invention will be described in more detail below with reference to Production Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. In each example, "parts" means parts by mass, and "%" means % by mass.
[0055] [Manufacturing of conductive pigment paste] <Examples 1 to 21 and Comparative Examples 1 to 8> The pigment dispersion resin (A), conductive pigment (B), solvent (C) and other components shown in Tables 1 to 3 were mixed in the amounts shown in Tables 1 to 3, and then dispersed in a thin film swirling high-speed mixer (manufactured by Primix Corporation, product name: Filmix) or a ball mill for the times shown in Tables 1 to 3, to obtain conductive pigment pastes X-1 to X-29. The resin blend amounts in the tables are values of solid content. Tables 1 to 3 also show the particle size (peak number, average particle size (D50), particle size ratio, and evaluation test results (initial viscosity, dispersibility, storage stability, finish, and conductivity). The moisture content of each of the conductive pigment pastes X-1 to X-29 was measured by Karl Fischer coulometric titration method, and was all 0.1% by mass or less. In the present invention, it is important that the performance is excellent in all items in the evaluation test, and if any one of them is rated "D" (fail), the conductive pigment paste fails. In addition, for Comparative Example 8, the viscosity, dispersibility and storage stability were unacceptable, so the coating film was not evaluated (finished appearance and electrical conductivity).
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] [Constituents of conductive pigment paste] <Pigment dispersing resin (A)> Dispersion resin A: Vinyl acetate-vinyl alcohol copolymer (SP value: 12.4, hydroxyl group concentration: 21.4 mmol / g, weight average molecular weight: 20,000, saponification degree: 97.0 mol%) Dispersion resin B: Vinyl acetate-vinyl alcohol copolymer (SP value: 12.0, hydroxyl group concentration: 17.2 mmol / g, weight average molecular weight: 15,000, saponification degree 89.0 mol%) Dispersion resin C: Vinyl acetate-vinyl alcohol copolymer (SP value: 10.8, hydroxyl group concentration: 9.9 mmol / g, weight average molecular weight: 28,000, saponification degree 60.0 mol%) Dispersion resin D: Polyvinyl acetal (SP value: 10.0, hydroxyl group concentration: 15.8 mmol / g, weight average molecular weight: 20,000, acetalization degree 78% by weight) Dispersion resin E: Methylcellulose (SP value: 17.7, hydroxyl group concentration: 11.5 mmol / g, weight average molecular weight: 40,000)
[0060] <Conductive pigment (B)> Conductive pigment A: Carbon black (acetylene black) (average primary particle diameter 18 nm, BET specific surface area 210 m 2 / g, pH: 9) Conductive pigment B: Carbon black (acetylene black) (average primary particle diameter 26 nm, BET specific surface area 120 m 2 / g, pH: 9) Conductive pigment C: Carbon black (acetylene black) (average primary particle diameter 35 nm, BET specific surface area 68 m 2 / g, pH: 9) Conductive pigment D: Carbon black (acetylene black) (average primary particle diameter 50 nm, BET specific surface area 35 m 2 / g, pH: 9) Conductive pigment E: Carbon black (acetylene black) (average primary particle diameter 90 nm, BET specific surface area 15 m 2 / g, pH: 9) Conductive pigment F: Carbon black (acetylene black) (average primary particle diameter 110 nm, BET specific surface area 11 m 2 / g, pH: 9)
[0061] <Solvent (C)> DMAc: N,N-dimethylacetamide (SP value 11.2) NMP: N-methyl-2-pyrrolidone (SP value 11.1) PGME: Propylene glycol monomethyl ether (SP value 10.4)
[0062] <Film-forming resin (D)> PVDF: Polyvinylidene fluoride (weight average molecular weight: 1 million, SP value: 9.1)
[0063] <High polar low molecular weight component (E)> NaOH: Sodium hydroxide HCOOH: Formic acid
[0064] [|δA-δC|] The relationship between the solubility parameter ΔA of the pigment dispersion resin (A) and the solubility parameter ΔC of the solvent (C), |ΔA-ΔC|, is the absolute value obtained by subtracting the SP value of the solvent (C) from the SP value, which is ΔA of the pigment dispersion resin (A), and was calculated by the following formula. |δA-δC|=|SP value of pigment dispersion resin (A) - SP value of solvent (C)|
[0065] [Particle size] <Number of peaks> The conductive pigment paste was diluted with a corresponding solvent, and the volumetric particle size distribution was measured using a particle size distribution measuring device (Microtrack-Bell, product name Microtrack MT3000) using the laser diffraction scattering method to obtain a frequency distribution curve. The number of peaks (mountains) on the frequency distribution curve was then counted.
[0066] <Average particle diameter (D50)> The conductive pigment paste was diluted with a solvent, and the volume-based average particle size (D50) was calculated using a particle size distribution measuring device (Microtrack Bell, product name: Microtrack MT3000, laser diffraction scattering method).
[0067] <Particle size ratio> The above average particle size (D50) was taken as the average secondary particle size, and the ratio of this to the average primary particle size of the conductive pigment used was calculated using the following formula. Particle size ratio = average secondary particle size (nm) / average primary particle size (nm)
[0068] [Evaluation test] <Initial viscosity> The obtained pigment dispersion paste was measured using a cone and plate type viscometer (HAAKE, product name Mars2, diameter 35 mm, cone and plate with a 2° inclination) at a shear rate of 0.1 s -1 The viscosity was measured and evaluated according to the following criteria. A: Viscosity is lower than 1000mPa·s. B: Viscosity is 1000 mPa·s or more and lower than 5000 mPa·s. C: Viscosity is 5000 mPa·s or more and lower than 10000 mPa·s. D: Viscosity is 10,000 mPa·s or more.
[0069] <Dispersibility> The resulting pigment dispersion paste was evaluated for dispersibility according to the dispersibility test of JIS K-5600-2-5 using a grain gauge and the following criteria. S: Pigments are dispersed at less than 10 μm. Dispersibility is very good. A: The pigment is dispersed at a size of 10 μm or more and less than 15 μm. Dispersibility is good. B: The pigment is dispersed at a size of 15 μm or more and less than 20 μm. The dispersibility is somewhat good. C: The pigment is dispersed at 20 μm or more, but no aggregates can be visually confirmed. Dispersibility is somewhat poor. D: Aggregates are visually observed. Dispersibility is very poor.
[0070] <Storage stability (viscosity increase rate)> The obtained pigment dispersion paste was stored at 50°C for one month, and the initial viscosity was compared with the viscosity after storage. The viscosity was measured using a cone and plate viscometer (manufactured by HAAKE, product name Mars2, diameter 35 mm, cone and plate with a 2° inclination) at a shear rate of 1.0 s -1 The viscosity increase rate was calculated according to the following formula, and the storage stability was evaluated according to the following criteria. Viscosity increase rate (%) = viscosity after storage (mPa·s) / initial viscosity (mPa·s) × 100-100 S: The viscosity increase rate (%) after storage is less than 10%. A: The viscosity increase rate (%) after storage is 10% or more and less than 50%. B: The viscosity increase rate (%) after storage is 50% or more and less than 100%. C: The viscosity increase rate (%) after storage is 100% or more and less than 200%. D: The viscosity increase rate (%) after storage is 200% or more.
[0071] <Finishing quality> The appearance of the test plate obtained in the conductivity evaluation test described below was observed, and the finish was evaluated visually. S: Has a very uniform appearance. A: It has a uniform appearance. B: Although there are some areas that are visually recognized as being slightly uneven, the appearance is almost uniform. C: Unevenness was visible, and the result was somewhat poor. D: The appearance is obviously non-uniform and poor.
[0072] <Conductivity> Two strips of aluminum foil tape (Sumitomo 3M, No. 425) were attached in parallel at 3 cm intervals on a polypropylene plate (10 cm x 15 cm x 3 mm). Next, PVDF was added to the obtained conductive pigment paste so that the weight ratio of carbon to PVDF was 1:1, and the mixed paste was applied with an applicator between the aluminum foil tapes to a length of 5 cm and a dry film thickness of 15 μm. The mixture was left at room temperature for 2 minutes, and then heated and dried at 80°C for 10 minutes to create a dry coating film with a width of 3 cm, length of 5 cm, and film thickness of 15 μm. The resistivity of the dried coating film applied between the aluminum foil tapes was measured at 20°C and a relative humidity of 65% using a measuring device (manufactured by Yokogawa Measurement Co., Ltd., product name Digital Multimeter MODEL 73401), and the conductivity was evaluated according to the following criteria. A: The resistivity is less than 0.007 Ωm, and the conductivity is very good. B: The resistivity is 0.007 Ωm or more and less than 0.008 Ωm, and the conductivity is good. C: The resistivity is 0.008 Ωm or more and less than 0.09 Ωm, and the conductivity is somewhat poor. D: The resistivity is 0.009 Ωm or more, and the conductivity is very poor.
[0073] [Manufacturing composite paste (coating material) and coating film (electrode layer)] <Examples Y-1 to Y-21, Z-1 to Z-21> 100 parts of the conductive pigment paste obtained in Examples 1 to 21 were mixed with 50 parts of N-methyl-2-pyrrolidone as a solvent and lithium nickel oxide (LiNiO 2 ) was added, and the mixture was mixed and stirred for 60 minutes using a disper to obtain composite pastes (coating materials) Y-1 to Y-21 which became Examples Y-1 to Y-21. Next, the composite pastes (coating materials) Y-1 to Y-21 were applied to both sides of an aluminum foil (current collector) with an average thickness of 25 μm as the substrate using an applicator so that the dry film thickness was 5 μm, and then dried at a temperature of 150° C. for 40 minutes to obtain coating films (electrode layers) Z-1 to Z-21, which became Examples Z-1 to Z-21. The resulting coating films (electrode layers) all had a residual solvent amount of less than 1%, and were coating films (electrode layers) with good finish.
Claims
1. A conductive pigment paste containing a pigment dispersing resin (A), a conductive pigment (B), and a solvent (C), The conductive pigment paste is diluted with a solvent, and the average particle size (D50) obtained by volume-based particle size distribution measurement by a laser diffraction scattering method is 300 to 1200 nm; The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), The conductive carbon (B-1) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; The conductive carbon (B-2) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2 is satisfied, the ratio X1 / X2 between the two is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; A conductive pigment paste, comprising a conductive carbon (B-1) and a conductive carbon (B-2) in a content ratio of 1 / 99 to 99 / 1.
2. A conductive pigment paste containing a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), the pigment dispersing resin (A) has at least one polar functional group selected from the group consisting of an amide group, an imide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphoric acid group, a silanol group, and an amino group, and the concentration of the polar functional group in the pigment dispersing resin (A) is 10 to 23 mmol / g; The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), The conductive carbon (B-1) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; The conductive carbon (B-2) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2 is satisfied, the ratio X1 / X2 between the two is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; A conductive pigment paste, comprising a conductive carbon (B-1) and a conductive carbon (B-2) in a content ratio of 1 / 99 to 99 / 1.
3. A conductive pigment paste comprising a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), the solubility parameter δA of the pigment dispersing resin (A) and the solubility parameter δC of the solvent (C) have a relationship of |δA-δC|<2.0, The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), The conductive carbon (B-1) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; The conductive carbon (B-2) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2 is satisfied, the ratio X1 / X2 between the two is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; A conductive pigment paste, comprising a conductive carbon (B-1) and a conductive carbon (B-2) in a content ratio of 1 / 99 to 99 / 1.
4. A conductive pigment paste comprising a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), the solubility parameter δA of the pigment dispersing resin (A) is 9.3 or more, and the solubility parameter δC of the solvent (C) is 10.4 to 15.0; The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), The conductive carbon (B-1) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; The conductive carbon (B-2) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2 is satisfied, the ratio X1 / X2 between the two is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; A conductive pigment paste, comprising a conductive carbon (B-1) and a conductive carbon (B-2) in a content ratio of 1 / 99 to 99 / 1.
5. A conductive pigment paste comprising a pigment dispersion resin (A), a conductive pigment (B), and a solvent (C), Further, the conductive pigment (B) contains 0.01 to 1.0 mass % of a highly polar, low molecular weight component, The conductive pigment (B) contains conductive carbon (B-1) and conductive carbon (B-2), The conductive carbon (B-1) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; The conductive carbon (B-2) is acetylene black having a BET specific surface area of 10 to 250 m 2 / g; When the average primary particle size or average diameter of the conductive carbon (B-1) is X1 and the average primary particle size or average diameter of the conductive carbon (B-2) is X2, and X1>X2 is satisfied, the ratio X1 / X2 between the two is 1.2 to 2.5, and both X1 and X2 are 100 nm or less; A conductive pigment paste, comprising a conductive carbon (B-1) and a conductive carbon (B-2) in a content ratio of 1 / 99 to 99 / 1.
6. 6. The conductive pigment paste according to claim 1, wherein the content of the conductive pigment (B) is 60 mass% or more based on the solid content of the conductive pigment paste, and the total amount of the conductive carbon (B-1) and the conductive carbon (B-2) is 50 mass% or more based on the mass of the conductive pigment (B).
7. The conductive pigment paste according to any one of claims 2 to 6, wherein the conductive pigment paste is diluted with a solvent and has an average particle size (D50) of 300 to 1200 nm, the average particle size being measured by a volume-based particle size distribution measurement method using a laser diffraction scattering method.
8. The conductive pigment paste according to any one of claims 1 to 7, wherein the conductive pigment paste is diluted with a solvent and a frequency distribution curve obtained by measuring a volume-based particle size distribution by a laser diffraction scattering method has at least two peaks.
9. The conductive pigment paste according to any one of claims 1 and 3 to 8, wherein the pigment dispersion resin (A) has at least one polar functional group selected from the group consisting of an amide group, an imide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphate group, a silanol group, and an amino group, and the concentration of the polar functional group in the pigment dispersion resin (A) is 10 to 23 mmol / g.
10. The conductive pigment paste according to any one of claims 1, 2, and 4 to 9, wherein the solubility parameter δA of the pigment dispersion resin (A) and the solubility parameter δC of the solvent (C) satisfy the relationship |δA-δC|<2.
0.
11. 11. The conductive pigment paste according to claim 1, wherein the solid content of the pigment dispersion resin (A) is 0.1 to 20 mass%, based on the total amount of solids in the conductive pigment paste.
12. The conductive pigment paste according to any one of claims 1 to 3 and 5 to 11, wherein the solubility parameter δA of the pigment dispersing resin (A) is 9.3 or more, and the solubility parameter δC of the solvent (C) is 10.4 to 15.
0.
13. The conductive pigment paste according to any one of claims 1 to 4 and 6 to 12, further comprising 0.01 to 1.0 mass% of a highly polar, low molecular weight component based on the conductive pigment (B).
14. A composite paste comprising the conductive pigment paste according to any one of claims 1 to 13 and at least one electrode active material.
15. A coating film obtained by applying the conductive pigment paste according to any one of claims 1 to 13 to a substrate.
16. A battery electrode layer obtained by coating a current collector with the composite paste according to claim 14.
Citation Information
Patent Citations
Conductive paste
JP2018022598A
Auxiliary conductive agent dispersion, application thereof and manufacturing method therefor
JP2019061916A
Battery electrode and use thereof
WO2012053087A1
Conductive sheet, method for manufacturing same, carbon composite paste, carbon composite filler, conductive resin material, and conductive rubber material
WO2015064708A1